Double-blind randomized parallel-group clinical trial of efficacy of the combination fluoxetine plus modafinil versus fluoxetine plus placebo in the treatment of major depression - Abolfazli, Roya; Hosseini, Mahdi; Ghanizadeh, Ahmad; Ghaleiha, Ali; Tabrizi, Mina; Raznahan, Maedeh; Golalizadeh, Mousa; Akhondzadeh, Shahin (Depression and anxiety, 2011)
Background: There is growing interest in the identification of novel therapeutic agents for the treatment of affective disorders, with modafinil being one promising substance. The purpose of the present investigation was to compare the efficacy of a combination of fluoxetine plus modafinil with that of fluoxetine plus placebo in the treatment of major depression in a 6‐week double blind and placebo‐controlled trial. Methods: Forty‐six adult outpatients who met the DSM‐IV‐TR criteria for major depression participated in the trial. Patients had a baseline Hamilton Rating Scale for depression score of at least 18. Patients were allocated in a random fashion, 23 to fluoxetine 40 mg/day plus modafinil 400 mg/day (200 mg bid) (morning and evening) and 23 to fluoxetine 40 mg/day plus placebo. Patients were assessed at baseline and after 1, 2, 4, and 6 weeks after start of medication. Results: Forty‐four patients completed the trial. Fluoxetine+modafinil and fluoxetine+placebo significantly decreased the Hamilton Rating Scale score for Depression over the trial period. However, the combination of fluoxetine and modafinil was significantly superior over fluoxetine alone in the treatment of symptoms of major depression. The difference between the two treatments was significant as indicated by the effect of group, the between‐subjects factor (df = 1, F = 4.42, P = 0.046). There were no significant differences in the two groups in terms of observed side‐effects. Conclusion: These findings suggest modafinil as a well‐tolerated and potentially effective agent in combination with fluoxetine in the management of patients with major depression. Depression and Anxiety, 2011.  © 2011 Wiley‐Liss, Inc.